The effect of ballistic training on punch kinetics in trained boxers - Crouch, G.; Diggin, D.; King, D. (The Journal of Strength and Conditioning Research, 2021)
Purpose: To investigate the impact of ballistic training (BT) on punching force (PF). Methods: Forty-five subjects with a mean boxing experience of approximately 11.3 ± 7.9 months were recruited. Subjects were matched according to boxing experience and randomly assigned to either a control (CONTR; male n = 16, female n = 6, mean age = 27.4 ± 7.4 years, height = 185.0 ± 8.1 cm, mass = 87.1 ± 13.8 kg) or experimental (BT; male n = 12, female n = 11, mean age = 26.2 ± 4.0 years, height = 173.7 ± 8.3 cm, mass = 72.1 ± 13.3 kg) group. Data was collected before (pre-test) and after a 6-week training period (post-testing). After a standardized warm-up, subjects performed 5 maximum effort rear-hand punches to a wall mounted force plate covered by a 5 cm thick strike shield, while wearing 10 oz boxing gloves (Bertec, Model 4060-NC). Sixty-second recovery was given between efforts. Subjects performed all punches while standing on 2 force plates (AMTI, Model OPT464508-2000). Rear-hand punch kinetics were assessed using PF, rate of force development (RFD) and contact time (CT). Ground reaction forces (GRF) from the lead and rear legs were assessed to evaluate leg contributions to PF. PF was recorded as the normal force from the wall mounted force plate. Ground and wall-mounted force plates were synchronized using Vicon Nexus and all force data sampled at 1,000 Hz. Subjects were familiarized with testing procedures one-week before pre-test procedures. Subjects assigned to the BT group completed supervised training with loaded ballistic exercises twice per week for 6 weeks. Subjects assigned to the CONTR group completed a sham treatment of equal volume, with unloaded exercises performed at a slow and controlled tempo. Results: Interaction effects showed a 30% increase in PF (F (1,43) = 60.2; p < 0.001) and a 44% increase in RFD (F (1,43) = 18.8; p < 0.001) in the BT group over time. There was no significant change in PF and RFD in the CONTR group. Interaction effects showed no changes in CT (F (1,35) = 0.12; p > 0.05). Examination of resultant foot forces showed an increase in rearfoot resultant force in the BT group (8.21%), while the CONTR showed little change (0.41%). Statistical analysis revealed changes in lead (F (1,42) = 0.51; p > 0.05) and rear (F (1,38) = 2.20; p > 0.05) foot resultant forces were not significant between groups. Conclusions: Following the 6-week intervention, the BT group demonstrated a significant increase in punch kinetics (PF and RFD) when compared to the CONTR group. BT may have induced neuromuscular adaptations which increased the efficiency of skeletal muscle contractility, such as an enhanced rate of excitation-contraction coupling and contract-relax mechanisms. Further research is required to evaluate the effect of BT on elite-level boxers. Practical Applications: The ability to produce high force is a key variable in boxing performance, consequently, training to develop this ability should be a priority. Results from this study suggest that short-term BT likely improves punching kinetics. These findings support the use of boxing-specific BT exercises to enhance the high-speed end of the force velocity curve and subsequent punching force in combat athletes.